Genotype x environment interaction for age at first calving, scrotal circumference, and yearling weight in Nellore cattle using reaction norms in multitrait random regression models - Chiaia, H. L. J. [UNESP]; Lemos, M. V. A. de [UNESP]; Venturini, G. C. [UNESP]; Aboujaoude, C. [UNESP]; Berton, M. P. [UNESP]; Feitosa, F. B. [UNESP]; Carvalheiro, R. [UNESP]; Albuquerque, L. G. [UNESP]; Oliveira, H. N. de [UNESP]; Baldi, F. [UNESP] (Amer Soc Animal Science, 2015)
The aim of this study was to evaluate the effect of genotype x environment interaction (GxE) on age at first calving (AFC), scrotal circumference (SC), and yearling weight (YW) and to estimate genetic correlations between these traits in Nellore cattle using reaction norms in multitrait random regression models. In this study, 28,871, 41,386, and 89,152 records of Nellore cattle for AFC, SC, and YW, respectively, were used. The data were obtained from farms located in the north, northeast, midwest, and southeast regions of Brazil that participate in the DeltaGen Breeding Program. Environmental levels were defined as a function of contemporary groups, that is, animals born in the same herd and year, from the same management group (from birth to yearling), and of the same sex. Postweaning weight gain was used as a criterion to evaluate the environmental conditions for all traits. For reaction norm analyses, residual variances were modeled with homogeneous and heterogeneous classes. The model for SC and YW included the fixed effects of contemporary group and age of the animal as a covariate as well as random direct additive genetic and residual effects. The same model, excluding the covariate age of the animal, was used for AFC. The heritability estimates were low to high for AFC (0.09 to 0.50), high for SC (0.51 to 0.67), and moderate to high for YW (0.33 to 0.71). The genetic correlations (within each trait) along the environmental levels varied from -0.27 to 1.0 for AFC, from 0.73 to 1.0 for SC, and from 0.26 to 1.0 for YW. The genetic correlations between different traits in different environments varied from -0.14 to -0.60 between AFC and SC, from -0.05 to -0.32 between AFC and YW, and from -0.05 to 0.72 between YW and SC. The genetic correlations have had different magnitudes for AFC, SC, and YW, which could indicate the presence of GxE. The present results should support researchers and farmers in defining selection criteria to improve growth traits and sexual precocity. Our results suggest that animals for breeding have to be selected in the same environment and management conditions as their progeny will be reared.
Keywords: Age at first calving; Genetic correlation; Nellore; Reaction norm; Scrotal circumference; Yearling weight